2013
DOI: 10.3109/13816810.2013.766217
|View full text |Cite
|
Sign up to set email alerts
|

Complement Factor B Polymorphism and the Phenotype of Early Age-related Macular Degeneration

Abstract: The CFB (R32Q) polymorphism was associated with AMD characterized by small drusen only, and appeared to be protective of large drusen (OR 0.48/0.45) and of larger drusen covered area (OR 0.34). Furthermore, peripheral drusen were more frequently found (OR 2.27). This result supports the role of complement components and their polymorphisms in drusen formation and may enable a better understanding of AMD pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 44 publications
(69 reference statements)
0
14
0
1
Order By: Relevance
“…Bora et al in 2005, reported C3 and MAC complex depositions in neovessels in mice model of laser-induced choroidal neovascularization (CNV), while the C3 knock out (C3 −/− ) CNV mice showed an absence of neovascularization, with a reduced level of angiogenic factors, thereby suggesting complement component C3 as a pro-angiogenic factor (15). This was further supported by genetic association studies of complement proteins in AMD pathogenesis, where a strong association of CFB and CFH polymorphism was observed along with a strong deposition of complement components in the RPE-Bruch layer (16)(17)(18). Further, the deposition of C3 in the retinal microglia and macrophage population in the outer retinal layers was shown to induce retinal degeneration in a mouse model of AMD (19).…”
Section: Introductionmentioning
confidence: 86%
“…Bora et al in 2005, reported C3 and MAC complex depositions in neovessels in mice model of laser-induced choroidal neovascularization (CNV), while the C3 knock out (C3 −/− ) CNV mice showed an absence of neovascularization, with a reduced level of angiogenic factors, thereby suggesting complement component C3 as a pro-angiogenic factor (15). This was further supported by genetic association studies of complement proteins in AMD pathogenesis, where a strong association of CFB and CFH polymorphism was observed along with a strong deposition of complement components in the RPE-Bruch layer (16)(17)(18). Further, the deposition of C3 in the retinal microglia and macrophage population in the outer retinal layers was shown to induce retinal degeneration in a mouse model of AMD (19).…”
Section: Introductionmentioning
confidence: 86%
“…The risk of developing AMD was decreased in half for patients carrying at least one of the rare alleles for any of the previously mentioned CFB SNPs (Sun et al, 2012). In another study, CFB SNP rs641153 (R32Q) was seen only in patients with drusen ≤250 μm and appeared to be protective against the formation of larger drusen >250 μm (Mantel et al, 2014). A meta-analysis found that patients with CFB SNPs rs4151667 and rs614153 carrying the minor A allele had a significantly smaller likelihood of having AMD (OR=0.54 and 0.41 respectively) (Thakkinstian et al, 2012).…”
Section: Biomarkers In Heritability and Geneticsmentioning
confidence: 98%
“…Complement factor B (CFB) polymorphisms have shown to be protective against the development of AMD (Gold et al, 2006b; Mantel et al, 2014; Spencer et al, 2007; Sun et al, 2012; Thakkinstian et al, 2012). In the first steps of the alternative pathway, CFB is bound to C3b.…”
Section: Biomarkers In Heritability and Geneticsmentioning
confidence: 99%
“…pooled data from 19 studies which took place between 2006 and 2011 for 4 SNPs: rs9332739 and rs547154 for C2 gene and rs4151667 and rs641153 for CFB gene, suggesting that these alleles contribute to lowering the risk of AMD pathogenesis in Caucasian population by 2.0% to 6.0% [30]. Recently, it has been reported that complement factor B polymorphism (R32Q) correlates with early AMD but have protective effect on late AMD as seen in Caucasian population [31]. On the contrary, it has been reported in INDEYE study that polymorphisms in ARMS2/HTRA1 locus are significantly associated with early and late AMD but instead of this locus the complement factor components like C2, CFH and CFB have not been found to be associated with AMD [32].…”
Section: Genetics Of Amdmentioning
confidence: 99%